Optflux: an open-source software platform for in silico metabolic engineering - Rocha, I. (2010)
[Excerpt] OptFlux is an open-source, user-friendly and modular software aimed at being the reference computational tool for Metabolic Engineering (ME) applications. It allows the use of stoichiometric metabolic models for phenotype simulation and strain optimization purposes. Many different approaches have been used to aid in metabolic engineering efforts that take available models of metabolism together with mathematical tools and/or experimental data to identify metabolic bottlenecks or targets for genetic engineering. However, the rational design of microbial strains has been limited to the developers of the computational or mathematical techniques, since a platform that provides a user friendly interface to perform such tasks was not yet available. [...]